STUDYING APPROPRIATE USAGE OF PROVERBS IN ABDULLA KAHHAR’S STORIES USING SEMANTIC METHOD - Haydarova, Aziza Nabijon kizi; Khasanova , Yulduz Mukhtor kizi (Innovative Development in Educational Activities, 2024)
This article studies the appropriate usage of proverbs in the works, especially stories of Abdulla Kahhar, one of the great creators of Uzbek literature and storywriter. The purposes and tasks of using them in the story are considered and their importance is discussed using semantic analysis method. Ideas are clearly proven by giving examples from several stories of writer. In this article, the reader will increase the interest of young people in the work of Abdulla Kahhar and help them to develop their translation skills.